(untitled) (Journal of Educational Sciences, 2022)
The article deals with humanitarian knowledge, which is studied by identifying the so-called communicative-ethno-pedagogical competence (from Latin competentia - a range of issues in which a given person has knowledge, experience), its content, functions and role in human life. In our opinion, the basis of a person’s life in society, as we think, as a social being, is his/her communicative and ethno-pedagogical competence.If, in essence, we take into account that life activity is inextricably linked with communication, interaction, mutual understanding of people, then, as experience shows, in a multinational state, which is the Republic of Kazakhstan, we should talk about communicative and ethno-pedagogical competence.Without taking into account the well-being and potential of peoples, without the so-called developed system of observance of human rights and freedoms, without strengthening unity through a balance of interests and partnership of all ethno-national diversity, it is impossible to achieve a result. And thus, as it is, modern education should reasonably combine, on the one hand, the education of national self-consciousness in people, the rooting in the minds of future teachers of sacred concepts that determine the spiritual life of the nation (homeland, family, native language, people, its history, faith, spiritual culture of the ethnic group, etc.).On the other hand, as proven by experience, education should thus create favorable conditions for the inclusion of a person in the past and present of world culture based on human interaction in the system "I - social group - society - world civilization" in the spirit of tolerance, mutual respect, dialogue of cultures, open communication.Increasingly important in the life of Kazakhstani society, as time shows, belongs to the ethno-national concept, and education plays a special role in the formation of a spiritually sovereign and socially responsible personality of a citizen of a multi-ethnic country, based in its development on the spiritual traditions of ancestors, protecting the values developed in centuries-old history life-creation of Kazakh ethnic groups. Keywords: communicative-ethnopedagogical competence, ethnopedagogics, communication, competence, higher education, future teachers,polyethnic environment, ethnos.